Strategi Komunikasi Digital dalam Diseminasi Informasi Publik di Platform Instagram @fpd_dpr - Hanania Adinda; Hudi Santoso (Jurnal Kajian dan Penelitian Umum, 2026)
This study aims to analyze the digital communication strategy implemented by the Democratic Party Faction of the Indonesian House of Representatives (DPR RI) in disseminating public information through the Instagram platform @fpd_dpr. The study used a qualitative descriptive approach with data collection techniques through in-depth interviews with the media team, experts, and related parties in social media management. The results of the study indicate that Instagram is utilized as the main medium for political communication, performance transparency, and interaction with the public. The communication strategy implemented includes value proposition, segmentation, targeting, positioning (STP), operational and delivery processes, and measurement and feedback. The content is designed visually, concisely, informatively, and based on current issues to attract the attention of the audience, especially the younger generation who actively use social media. The effectiveness evaluation strategy is carried out through public engagement indicators, such as likes, comments, views, and audience responses to posts. Overall, the implemented digital communication strategy is considered quite effective in increasing public participation and expanding the reach of information, although it still faces challenges in adapting to the ever-changing dynamics of social media development.